INDIVIDUALITY AND LEADERSHIP REFLECTED IN RANDALL WALLACE’S SECRETARIAT - Primadany, Risma Sinta (LANTERN (Journal on English Language, Culture and Literature), 2017)
Secretariat is a movie which tells about the life of Penny Chenery in leading her Meadow Stable. Secretariat is the name of a horse owned by Chenery’s family who can bring the business into success by winning many race competitions. The main character, Penny Chenery, is the person who continues leading her parent’s business. The aims of this thesis are to describe the intrinsic aspects which are narrative elements (characters, setting, conflict) and cinematic elements (camera distance, angle, mise-en-scene, and sound) and to analyze the extrinsic aspect which is individuality and the style of leadership reflected by the character Penny Chenery in Secretariat by applying Individualism theory and Path Goal Leadership theory. The writer applies library research and social psychology approach for her research. In this research, the writer finds out that Penny Chenery reflects individuality and four style of leadership in Path Goal Leadership theory.